A 9,000-year record of Chagas' disease - Aufderheide, Arthur C. (National Academy of Sciences, 2004)
Tissue specimens from 283 principally spontaneously (naturally) desiccated human mummies from coastal and low valley sites in northern Chile and southern Peru were tested with a DNA probe directed at a kinetoplast DNA segment of Trypanosoma cruzi. The time interval spanned by the eleven major cultural groups represented in the sample ranged from ≈9,000 years B.P. (7050 B.C.) to approximately the time of the Spanish conquest, ≈450 B.P. (≈1500 A.D.). Forty-one percent of the tissue extracts, amplified by the PCR reacted positively (i.e., hybridized) with the probe. Prevalence patterns demonstrated no statistically significant differences among the individual cultural groups, nor among subgroups compared on the basis of age, sex, or weight of specimen tested. These results suggest that the sylvatic (animal-infected) cycle of Chagas' disease was probably well established at the time that the earliest humans (members of the Chinchorro culture) first peopled this segment of the Andean coast and inadvertently joined the many other mammal species acting as hosts for this parasite.